ANALYSIS OF THE POLICY OF SENDING THE GARUDA CONTINGENT TO LEBANON IN THE UNIFIL UN MISSION FOR THE 2021-2024 PERIOD - Shanika, Kurnia Rafif; Jatmika, Muhammad Indrawan (FISIP Universitas Malikussaleh, 2025)
Every country has its own foreign policy. Foreign policy is used by a country to behave respond to conflicts that occur in the international world, according to its interests. Indonesia as a country is no different. The policy provided can be in the form of foreign aid support or just a neutral, pro or contra attitude. Indonesia has always played an active role in responding to international phenomena and their escalation. One of the international conflicts that Indonesia has actively contributed to is the conflict in Lebanon involving the militant group Hezbollah and Israel. The conflict in Lebanon has been going on for a long time, but recently the conflict has escalated again. Indonesia, as a country that strongly opposes war and colonization, was certainly moved to see this. Indonesia decided to help by continuing to send Garuda Contingent security forces assistance, in the UNIFIL (United Nations Interim Force In Lebanon) mission under the auspices of the UN (United Nations). Behind Indonesia’s foreign policy in continuing to send security force assistance, there must be many considerations. There are projections of values, norms, and identities that want to be maintained. In addition, maintaining this policy does not rule out of the possibility of opening up other opportunities that are beneficial to Indonesia.